Forfeiture and prohibition of animal ownership under Polish criminal law: key theoretical and practical implications - Welz, Kinga (Studia Iuridica Toruniensia, 2025)
The article analyzes the institution of animal forfeiture in Polish criminal law, highlighting its distinct nature compared to the forfeiture of material objects. In the context of the case of the cat Dżizas, the author presents the complexity of the legal, ethical, and social issues associated with this penal response measure. Particular attention is given to the distinction between mandatory and discretionary forfeiture, as well as to the issue of animals’ legal autonomy in the context of their protection. The article emphasizes the need for further dereification of animals and the appropriate application of legal provisions aimed at safeguarding their welfare, while also considering potential social consequences for the offender’s environment.